The effect of hot money on stock exchange index exchange rates and interest rates: The case of Turkey - Gamze Şekeroğlu; Melek Acar Boyacioğlu (CES Working Papers, 2020)
Hot money flows refer to short-term foreign currencies entering the country's economies through short-term loans and portfolio investments. The purpose of the study is to determine the impact of hot money flows in Turkey on stock exchange index, exchange rates and interest rates. For this purpose, BIST-100 Index closing values, US dollar exchange rates and five-year Treasury bond interest rates were considered to explain hot money data. The data are in an annual frequency and the analyses were made for the period between 1989 and 2019. The structural equation model was applied in the study. The model fit index values that helped to determine the success rate of the established model was examined before passing on to the analysis. According to the model fit index values, it was determined that the model was compatible with the data. It was found that hot money has a positive effect on the stock exchange index and a negative effect on interest rates and exchange rates.
Keywords: 330; hot money; exchange rate; interest rate; stock exchange index; structural equation model